2019
DOI: 10.3233/jad-180728
|View full text |Cite
|
Sign up to set email alerts
|

Resting Cerebral Blood Flow After Exercise Training in Mild Cognitive Impairment

Abstract: Background: Exercise training has been associated with greater cerebral blood flow (CBF) in cognitively normal older adults (CN). Alterations in CBF, including compensatory perfusion in the prefrontal cortex, may facilitate changes to the brain’s neural infrastructure. Objective: To examine the effects of a 12-week aerobic exercise intervention on resting CBF and cognition in CN and those with mild cognitive impairment (MCI). We hypothesized individuals with MCI (vs. CN) would exhibit greater whole brain CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 85 publications
(87 reference statements)
8
90
0
Order By: Relevance
“…Previous research has shown that cognitive performance (e.g., information processing speed, memory, executive function) declines with advancing age [4][5][6]. Age-related impairments also reflect brain atrophy and decreased brain function in several regions, including the prefrontal and temporal cortices, and the hippocampus [7][8][9]. As such, the healthcare field must identify novel therapeutic strategies to combat the rising rate of age-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that cognitive performance (e.g., information processing speed, memory, executive function) declines with advancing age [4][5][6]. Age-related impairments also reflect brain atrophy and decreased brain function in several regions, including the prefrontal and temporal cortices, and the hippocampus [7][8][9]. As such, the healthcare field must identify novel therapeutic strategies to combat the rising rate of age-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…CRF‐related benefits are not confided to the cardiovascular function and rather extend to the cerebrovascular system (Lucas et al, ; Tarumi and Zhang, ). For instance, aerobic exercise training alters favorably cerebrovascular health in varying clinical conditions ranging from chronic obstructive pulmonary disease (Lewis et al, ), cognitive impairments (Alfini et al, ), stroke (Ivey et al, ) and following cancer (Northey et al, ). Evidence show that life‐long aerobic training individuals with elevated CRF have higher resting intracranial blood velocity in the anterior circulation (as indexed by transcranial Doppler sonography of mean blood velocity in middle cerebral artery (MCAv mean ) (Ainslie et al, ; Bailey et al, ), and in the posterior circulation (as indexed by arterial spin labeling in posterior cingular cortex/precuneus) (Thomas et al, ) and higher extracranial blood flow (as indexed by carotid Doppler) (Braz et al, ) than their sedentary counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings in APP/PS1 mice, however, recent studies in patients with dementia (diagnosed as mild to moderate AD in Refs. [83] and [84]) showed that 3 times per week 60 min of aerobic exercise led to improved cognition [83, 85, 86], but this effect was not correlated with increased cerebral blood flow [84, 87]. Finally, we did not observe changes in the density or geometry of cortical capillaries in APP/PS1 mice that exercised, compared to sedentary controls.…”
Section: Discussionmentioning
confidence: 66%